Peningkatan Produktivitas dan Penjualan pada UMKM Pakaian Muslimah Ummu Syuraih di Kecamatan Medan Marelan - Lily Karlina Nasution; Mayang Murni; Ika Sari Dewi (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2020)
Intense competition requires MSMEs to be active in innovating both in terms of products, marketing and business development. MSME Ummu Syuraih produces Muslim clothing, khimar and niqab. MSME Ummu Syuraih also facing several problems in running its business including the using of financial management manually,lacking of HR capabilities and production machinery, using a mouth to mouth marketing and displaying less attractive product packaging. The purposes of this community service activity is to 1) manage the MSME Ummu Syuraih business financial management professionally, 2) increase the capacity of products through enhancing the expertise and skills of its HR, 3) expand the marketingnetwork for the products through the right marketing mix strategy, 4) improve the display of the packaging of the products. Activities in community service include training (sewing skills, marketing and financial management by using application and website), assistance (using financial management application and website), and tool grants. Based on the implementation and evaluation of the activities, it can be concluded that SMSE Ummu Syuraih can manage her business professionally and there is an increase in production and sales capacity due to the increase of customers demand.